RANCANG BANGUN PENDINGIN OTOMATIS PADA SAMBUNGAN PLAT BAJA GULUNGAN (HOT ROLL COIL) PASCA PENGELASAN - Mubarak, Abdul Haris (Jurusan Teknik Mesin Fakultas Sains dan Teknik Universitas Bangka Belitung, 2025)
This research aims to create an automatic cooling device for rolled steel joints (Hot Roll Coil) produced by a nickel processing factory operating in the Morowali Industrial Area. Steel plates in the form of long rolls that are rolled are first welded to connect the steel plates to produce rolls of steel plate that are ready to be marketed. Joining steel using this welding method makes the steel plate hot with a temperature in the range of 100°C-200°C. The temperature of the steel plate after welding must be immediately lowered before rolling, because otherwise the steel joints will come apart and could hamper the production process because the broken plate will have to repeat the welding process from the beginning. The plate temperature required to enter the rolling process is 40°C - 60°C. This research has produced a tool to cool steel joints by automatically spraying the steel joints and succeeded in reducing the plate temperature from 100℃ - 200℃ to a constant temperature of 40℃ - 50℃ according to the required temperature.